A poética interdisciplinar de Jocy de Oliveira - Rahmeier, Lazlo (2014)
The central theme of this work is the poetics of Jocy de Oliveira. The research seeks, through a case study with the artist, to analyze her production process, the factors that affect, influence and provoke her art making activity. For this purpose, the historical and cultural contexts in wich Jocy de Oliveira falls are analyzed, and the compositional techniques and elements that the artist uses in her work are identified. As instruments for data collection, it was used newspaper reports, websites, brochures and videos; informal conversations and semi-structured interviews with the artist; and participant observation in the assembly of one of her works. The results of the research show that Jocy de Oliveira´s work involves music, text, visual and theatrical elements, thus becoming an interdisciplinary artwork that incorporates various languages and technologies; they also show that her technical and aesthetic bases are anchored in the musical vanguard born in Europe after the Second World War. Outstands in her work the electroacoustic soundscape, the electronic means of sound production, the techniques for extending acoustic instruments, the vocal expression, the chance, the spatial projection of the sound, the intuitive music, the ceremonies and rituals of different cultures, the nature, the cosmos, and the woman, a central theme throughout her work.